2015
DOI: 10.1051/0004-6361/201424794
|View full text |Cite
|
Sign up to set email alerts
|

A search for TiO in the optical high-resolution transmission spectrum of HD 209458b: Hindrance due to inaccuracies in the line database

Abstract: Context. The spectral signature of an exoplanet can be separated from the spectrum of its host star using high-resolution spectroscopy. During these observations, the radial component of the planet's orbital velocity changes, resulting in a significant Doppler shift that allows its spectral features to be extracted. Aims. In this work, we aim to detect TiO in the optical transmission spectrum of HD 209458b. Gaseous TiO has been suggested as the cause of the thermal inversion layer invoked to explain the daysid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 37 publications
(68 reference statements)
6
122
2
Order By: Relevance
“…While it is likely that the abundances of these molecules are too low for these data to constrain (see e.g., Madhusudhan 2012;Moses et al 2013 for typical abundances of hot Jupiter atmospheres as a function of temperature and C/O ratio), we do not rule out that incorrect line positions in the line list used to create the models are responsible for their non-detection. Hot methane and other line lists are known to have inaccuracies (Hargreaves et al 2015), particularly at high resolution (Hoeijmakers et al 2015). Brogi et al (2013) tentatively reported molecular absorption from carbon monoxide and water in the atmosphere of 51 Peg, using observations with CRIRES/VLT at m 2.3 m in the same month as the observations presented here.…”
Section: Atmospheric Properties Of the Planetmentioning
confidence: 53%
“…While it is likely that the abundances of these molecules are too low for these data to constrain (see e.g., Madhusudhan 2012;Moses et al 2013 for typical abundances of hot Jupiter atmospheres as a function of temperature and C/O ratio), we do not rule out that incorrect line positions in the line list used to create the models are responsible for their non-detection. Hot methane and other line lists are known to have inaccuracies (Hargreaves et al 2015), particularly at high resolution (Hoeijmakers et al 2015). Brogi et al (2013) tentatively reported molecular absorption from carbon monoxide and water in the atmosphere of 51 Peg, using observations with CRIRES/VLT at m 2.3 m in the same month as the observations presented here.…”
Section: Atmospheric Properties Of the Planetmentioning
confidence: 53%
“…This is also a motivation for building a high-resolution spectrograph on the European Extremely-LargeTelescope such as HiReS and METIS (Udry et al 2014;Brandl et al 2014;Snellen et al 2015). In the meantime, extensive studies have to be made with existing facilities and data especially in the optical domain (e.g., Hoeijmakers et al 2015) to help observers make the best use of future facilities. Our study is a significant step in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…They do not find any emission signature required to confirm a thermal inversion in the atmosphere of HD 209 458b. Hoeijmakers et al (2015) suggest that their TiO opacity data was insufficient to reach any conclusion regarding a thermal inversion on HD 209 458b. These conclusions, however, are based on the assumption that the featured molecules are associated with a thermal inversion and not with another process that affects, for example, their abundance.…”
Section: Introductionmentioning
confidence: 91%